2013
DOI: 10.1161/hypertensionaha.111.00572
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Angiotensin Receptor-Associated Protein in Renal Tubule Suppresses Angiotensin-Dependent Hypertension

Abstract: We have previously shown that angiotensin II type 1 receptor-associated protein (ATRAP/Agtrap) interacts with the angiotensin II type 1 receptor and promotes constitutive internalization of the receptor so as to inhibit the pathological activation of its downstream signaling but preserve baseline physiological signaling activity. The present study was designed to investigate the role of renal ATRAP in angiotensin II–dependent hypertension. We generated transgenic mice dominantly expressing ATRAP in the renal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 38 publications
(37 reference statements)
3
63
0
Order By: Relevance
“…Of the six Agtrap-Plod1 genes, only three (Agtrap, Nppa, and Mthfr) were previously reported to have BP or renal phenotypes (John et al 1995;Yi and Li 2008;Wakui et al 2013), but none had been systematically examined in a uniform genetic background that is susceptible to hypertension. Using a ZFN rat strategy, we found that Nppa, Clcn6, Mthfr, Plod1, and Agtrap mutations caused divergent CVD phenotypes and have the ability to modify renal phenotypes independently of BP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six Agtrap-Plod1 genes, only three (Agtrap, Nppa, and Mthfr) were previously reported to have BP or renal phenotypes (John et al 1995;Yi and Li 2008;Wakui et al 2013), but none had been systematically examined in a uniform genetic background that is susceptible to hypertension. Using a ZFN rat strategy, we found that Nppa, Clcn6, Mthfr, Plod1, and Agtrap mutations caused divergent CVD phenotypes and have the ability to modify renal phenotypes independently of BP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally and most importantly, the fact that a very high ATRAP expression (33-fold mRNA increase in distal tubules and 10-fold protein increases in total kidney homogenates) was necessary to reduce the response to Ang II suggests that ATRAP effects may be minor. Regardless of the previous observations, the study by Wakui et al 5 emphasizes the tremendous impact of the kidneys in the hypertensive response to Ang II, while highlighting the potential of ATRAP as a negative modulator. The authors present interesting evidence for the tuning down effect of ATRAP on Ang II actions to increase sodium avidity in the nephron.…”
Section: Giani Et Al Atrap and Ang Ii-induced Hypertension 1151mentioning
confidence: 89%
“…Detailed analysis of renal ATRAP expression in their mutant strain revealed that distal regions of the nephron, from the distal to connecting tubules, were the sites of highest expression for the transgenic protein. The most important observation by Wakui et al 5 is that ATRAP overexpression in the distal nephron blunted the pressor response to Ang II. In their experiments, the basal systolic blood pressure of the transgenic mice and wild-type mice was similar.…”
mentioning
confidence: 98%
See 2 more Smart Citations